ANALISIS SISTEM DAN PROSEDUR AKUNTANSI PERSEDIAAN OBAT- OBATAN (Studi Kasus pada Rumah Sakit Umum Daerah Kota Malang) - GITA DWI ARIANI PUTRI (Jurnal Ilmiah Mahasiswa FEB, 2016)
The research purposes to explain how inventory accounting system in a public institution, particularly in a hospital, runs well in terms of analysis on the applied inventory system and procedure. The Regional Public Hospital of Malang is one of business units owned by the government which provides health services. Most of the healing and recovery activities at the hospital rely on the available medicine inventory; therefore, inventory management, monitoring,  and  control is  highly required  to guarantee optimum use of  the healthcare inventory. The result of the study shows that the inventory accounting system and procedure of the Regional Public Hospital of Malang has been well-implemented because the institution uses the supporting data for such system and  procedure covering the functions related, information needed by the management, documents used, and accounting statement structured. However, lack of fixed official procedure to administer physical count process on the  inventory  becomes  a  weakness  which  might  affect  the  accuracy  of the  provided information regarding the inventoryKeywords: Stock accounting system, Physical count